Effect of Heat Treatment on the phase purity of Fe2P Powder - Singh A.K.; Singh V.; Bhattacharjee S.; Lee S.-C.; Singh S.; Pandey D. (My University, 2025)
Structural studies of Fe2P powder is done using X-ray diffraction data. In addition to the pure hexagonal phase, we noticed the existence of an additional phase in pristine Fe2P powder. The additional phase is found to be Fe3P-type tetragonal phase as confirmed by two phases Rietveld analysis of XRD data of ball milled powder. The heat treatment method used to get homogeneous Fe2P phase which is hexagonal. The current findings are important as they can affect the physical properties such as magnetoelastic coupling and magnetocaloric effect. © 2020 American Institute of Physics Inc.. All rights reserved.